ผลกระทบของการกำกับดูแลกิจการ ประสิทธิภาพ และพฤติกรรมทางการเงินของบริษัท ต่อผลการดำเนินงานของอุตสาหกรรมบริษัทประกันวินาศภัยในประเทศไทย - จุฑาทิพย์ สุรวัฒนบูรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research aims to study the impact of corporate governance, efficiency and financial behavior on firm performance of the non-life insurance industry. The results of the study can be applied as a guideline for improving the operation of the non-life insurance companies in Thailand. This study obtained data from annual reports of the listed non-life insurance firms during 2006-2007 and 2009-2010. Data Envelopment Analysis (DEA) is utilized to calculate efficiency and multiple linear regression models are used to analyze the impact of factors. The results indicate that board independence, total efficiency and profit margin shows a positive impact on firm performance. This relationship is also statistically significant. It means that if board independence, total efficiency and profit margin increase, firm performance will also increase. But in the meanwhile, expense ratio is statistically significant and negatively related to firm performance. It means that if expense ratio decreases, firm performance will increase.